Monoclonal antibodies against CGRP in migraine prevention: current state of knowledge - Wieleba, Marcin; Witczak, Katarzyna Wiktoria; Woźniak, Weronika Maria; Winiarska, Zuzanna; Wiercioch, Eliza; Włodarczyk, Franciszek; Krupska, Barbara Izabela; Zapalska, Magdalena; Kulig, Lidia; Malec, Julia Anna (Quality in Sport, 2026)
Background. Migraine is one of the most common neurological disorders and has a significant impact on patients’ quality of life. In recent years, growing attention has been directed toward targeted therapies focused on the calcitonin gene-related peptide (CGRP) pathway, which represent a novel option in migraine prevention. Aim. The aim of this study was to present the current state of knowledge regarding the use of monoclonal antibodies targeting CGRP in migraine prevention, with particular emphasis on their mechanisms of action, clinical efficacy, and safety profile. Materials and methods. A narrative literature review was conducted using the PubMed and Scopus databases. Publications from recent years were included, encompassing original studies, systematic reviews, and meta-analyses addressing anti-CGRP monoclonal antibody therapy in migraine treatment. Results. Available evidence indicates that monoclonal antibodies targeting the CGRP pathway effectively reduce the number of migraine days and improve patients’ quality of life, including in individuals who are resistant to previous preventive therapies. Sustained therapeutic effects have also been observed in long-term follow-up. These therapies are characterized by a favorable safety profile, with adverse events typically being mild in nature. However, the available findings remain partly heterogeneous, and data concerning specific patient populations are still limited. Conclusions. Anti-CGRP monoclonal antibodies represent an effective and well-tolerated option for the preventive treatment of migraine. Their use may significantly improve disease control, particularly in patients with an inadequate response to previous therapies. However, further studies are required to evaluate long-term safety and to optimize therapeutic strategies.